Implications of rituximab pharmacokinetic and pharmacodynamic alterations in various immune-mediated glomerulopathies and potential anti-CD20 therapy alternatives - Hartinger, Jan Miroslav; Kratky, Vojtech; Hruskova, Zdenka; Slanar, Ondrej; Tesar, Vladimir (Frontiers in Immunology, 2022)
The specific B-cell depleting anti-CD20 monoclonal antibody rituximab (RTX) is effective in the treatment of various immune-mediated glomerulopathies. RTX administration was shown to be reliable and highly effective particularly in patients with ANCA-associated vasculitis, which predominantly manifests with non-nephrotic proteinuria. In these patients, stable long-term B-cell depletion is usually readily achieved by standard dosing regimens. However, in patients with nephrotic syndrome, RTX pharmacokinetics is profoundly altered and RTX does not keep high enough levels for a sufficiently long period, which may render RTX treatment ineffective. This may be more serious problem in patients with membranous nephropathy with non-selective proteinuria compared to minimal change disease with preserved protein selectivity. As complement derived cytotoxicity is important mode of action of RTX, hypocomplementemia frequently associated with systemic lupus erythematodes may hamper RTX efficacy in the treatment of patients with lupus nephritis. This review describes RTX pharmacokinetics and pharmacodynamics in several selected glomerulopathies as well as the effect of proteinuria, anti-drug antibodies and other clinical variables on RTX clearance and volume of distribution. The effect of plasmapheresis and peritoneal dialysis on RTX clearance is also discussed. Possible association between pharmacokinetics and pharmacodynamics alterations in different kidney affecting glomerular diseases, sustainability of B-cell depletion and clinical efficacy of RTX is reviewed and possible dosing implications are proposed. The role of therapeutic drug monitoring in treatment tailoring is discussed. Various already tested RTX dosing schedules are compared in terms of clinical and laboratory treatment responses. As alternative anti-CD20 molecules may also be effective in RTX unresponsive patients, their pharmacokinetics, pharmacodynamics and current role in the treatment of glomerulopathies are also mentioned.